Historical insights into modern corruption: descriptive moralities and cooperative corruption in an Indian city. Issue 2 (2nd April 2016) - Pani, Narendar
ABSTRACT: Much of the debate on the relationship between social norms and corruption has been confined to comparisons across countries. But a gap between what is morally acceptable by a society and what is legally correct can exist within individual countries as well. In such cases, it is possible for individual acts of corruption to be seen to be morally justified. This paper explores the emergence of this gap through the imposition of British law on a very different descriptive morality in nineteenth century Indian city of Bengaluru. Drawing from this experience it seeks to identify the dynamics of the process in a way that would allow for it to be used to understand corruption across different societies, and the lessons it has for an effective strategy against endemic corruption.